2013
DOI: 10.1212/wnl.0b013e31829d873c
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of statin therapy associates with Parkinson disease

Abstract: Continuation of lipophilic statin therapy was associated with a decreased incidence of PD as compared to discontinuation in statin users, especially in subgroups of women and elderly. Long-term follow-up study is needed to clarify the potential beneficial role of lipophilic statins in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 35 publications
4
118
1
Order By: Relevance
“…Of the included studies, 6were from North America [14, 18-20, 22, 26] 4 were from Europe [8, 9, 17, 24], and 3 were from Asia [21, 23, 25]. The year of publication ranged from 2007 to 2016, thus spanning 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 6were from North America [14, 18-20, 22, 26] 4 were from Europe [8, 9, 17, 24], and 3 were from Asia [21, 23, 25]. The year of publication ranged from 2007 to 2016, thus spanning 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Previous clinical studies revealed that Sim has the potential to decrease the risk of PD by lowering oxidative stress [12,13], and it can also affect the suppressive potential of pathological alpha-Syn by lowering cholesterol levels [14]. The fact that Sim can cross the blood-brain barrier as well as the considerable evidence supporting the beneficial effects of Sim on the central nervous system make Sim one of the more promising drugs for treating neurodegenerative diseases, including stroke [15,16] and PD [17,18]. Earlier investigations confirmed that ROS is produced during the maintenance of an essential metabolic balance in the body, as a series of anti-oxidant mechanisms stabilize the redox balance of cells [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A populationbased study by Lee et al, indicated that the continuation of lipophilic statin, such as atorvastatin and simvastatin, therapy was associated with a decreased incidence of PD (Lee et al, 2013). During 12 years of follow-up (1994-2006) study, Gao et al, found that the regular statin medication was correlated to a reduction in PD risk .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lowering cholesterol, statins have gradually been used to reduce the risk of heart attack, cerebral ischemia, and have been demonstrated to exert potential beneficial effects in different neurological diseases (Wang et al, 2007;Keener & Sanossian, 2008;van der Most et al, 2009;Sugawara et al, 2011;Ayer et al, 2013). Although the precise mechanisms are unclear and contrasting results have been observed (Reiss & Wirkowski, 2007;Becker et al, 2008), additional studies have found that statins display important effects on cognitive related neurological diseases such as PD van der Most et al, 2009;Wang et al, 2011;Lee et al, 2013;Xu et al, 2013). If statins would have a potentially useful impact on impaired memory regulation in the progression of PD, this presents an interesting challenge.…”
Section: Introductionmentioning
confidence: 99%